Optimization of real-time PCR protocols from lymph node bovine tissue for direct detection of Mycobacterium tuberculosis complex - Eduardo Vera-Salmoral; Jaime Gómez-Laguna; Ángela Galán-Relaño; Inés Ruedas-Torres; Librado Carrasco; Inmaculada Luque; Belén Huerta; José María Sánchez-Carvajal (Microbiology Spectrum, 2023)
ABSTRACT Bovine tuberculosis (bTB) is a zoonotic disease and a global health problem that is subjected to obligatory eradication programs in the European Union. Microbiological culture is an imperfect technique for bTB diagnosis. This study aims to compare and validate two DNA isolation protocols and three different specific DNA targets, IS6110, IS4, and mpb70, to confirm Mycobacterium tuberculosis complex (MTC) infection by real-time PCR directly from fresh tissue samples. Fresh lymph node samples were collected from 81 cattle carcasses at the slaughterhouse. A comparison of both extraction protocols was performed with IS6110-real-time PCR, showing an adjusted sensitivity (SE) of 78.34% and 95.9% for protocols 1 and 2, respectively, while the specificity (SP) was 100% in both cases. Afterward, the comparison between IS4 and mpb70 targets was performed from the samples extracted with protocol 2, obtaining an adjusted SE of 90.87% and 83.3%, respectively, and an SP of 100% in both cases. The positive likelihood ratio was ∞ for the three targets, and the negative likelihood ratio was 0.04, 0.091, and 0.16 for IS6110, IS4, and mpb70, respectively. Negative predictive values were ≥90%, ≥85%, and ≥80% for real-time PCR targeting IS6110, IS4, and mpb70, respectively, when the true prevalence is ≤60%, and the positive predictive value is 100% in any scenario of true prevalence. According to these results, the DNA extraction protocol 2 and real-time PCR targeting IS6110 or IS4 could be potential first-choice molecular assays to detect MTC directly in fresh bovine tissue samples. Importance Bovine tuberculosis (bTB), a chronic infectious and zoonotic disease caused by Mycobacterium tuberculosis complex (MTC), is considered a neglected disease of global importance, causing a detrimental impact on public health, particularly in developing countries where tuberculosis remains a major health problem. However, debate around the efficacy of control measures is still an ongoing matter of concern, with poor diagnostic performance being considered one of the most relevant factors involved in the failure to eradicate the disease since many truly infected animals will be misclassified as bTB-free. This study highlights a DNA extraction protocol and real-time PCR targeting IS6110 or IS4 as potential first-choice molecular assays to detect MTC directly in fresh bovine tissue samples, providing rapid, highly sensitive, and specific diagnostic tools as an alternative to microbiology, which could take up to 3 months to complete, shortening the turnaround time for decision makers to be promptly informed.